Digital library acceptance and continued use: conceptual framework / Abd Latif Abdul Rahman and Adnan Jamaludin - Abdul Rahman, Abd Latif; Jamaludin, Adnan (Universiti Teknologi MARA, Kedah, 2017)
At present, users are already relying on the availability of the digital library for their information needs to support their daily tasks. In the context of the university environment, the digital library in the university is being utilized by students and academics almost all the time. This is because their learning and teaching activities involve using information resources which are offered by the digital library. As such, the digital library in universities is not only playing an important role but it will also become one of the most sophisticated and important information systems supporting the universities’ activities. In this context, librarians and information professionals who are responsible for the development of the digital library need to understand the intricacies of it so that the advantages and benefits can be exploited for the betterment of library and information service provisions. One of the most important aspects about the digital library in the university environment is its acceptance and usage by the university community, particularly the students. The success of the digital library is only as good as its acceptance and usage by the users and as such, it is crucial to investigate and understand not only its acceptance and usage, but also how and why it is being accepted and used. In other words, variables that are deemed important that may have some influences on the acceptance and use of digital library need to be examined. Therefore, this paper develops a conceptual framework on digital library acceptance which includes Performance Expectancy, Effort Expectancy, Information Quality and Digital Library Services as a predictor of continued use of digital library. Because the digital library is one of the most significant technologies in the field of library and information science, this proposed model would contribute significant benefits for librarians and information professionals at large. Furthermore, with the dearth of research in this area, the proposed model would contribute with a better understanding of the extent to which the digital library is being accepted and continued used, through an analysis of the factors involved and how they interact with each other. With these insights, professionals can improve and enhance the services of the digital library so that users could obtain the optimum benefit.